Pingchan Granule for Motor Symptoms and Non-Motor Symptoms of Parkinson’s Disease: A Randomized, Double-Blind, Placebo-Controlled Study - Gu, Si-Chun; Ye, Qing; Wang, Chang-De; Zhao, Shao-Rong; Zhou, Jie; Gao, Chen; Zhang, Yu; Liu, Zhen-Guo; Yuan, Can-Xing (Frontiers in Pharmacology, 2022)
Background: Pingchan granule (PCG) is a traditional Chinese medicine for treating Parkinson’s disease (PD). Objective: This study aimed to evaluate the efficacy and safety of PCG for motor and non-motor symptoms of PD. Methods: In this multicenter, randomized, double-blind, placebo-controlled trial, 292 participants with mild-to-moderate PD were included and followed for 36 weeks (24-week treatment, 12-week follow-up after intervention), randomly assigned at a 1:1 ratio to receive PCG or placebo. The primary outcomes included the severity of motor symptoms assessed by Unified Parkinson’s disease Rating Scale (UPDRS) part 3 (UPDRS-III) score and the rate of disease progression assessed by total UPDRS score. Secondary outcomes included non-motor symptoms assessed using the Scale for Outcomes in Parkinson’s Disease-Autonomic (SCOPA-AUT), Parkinson’s disease Sleep Scale (PDSS), 24-item Hamilton Rating Scale for Depression (HAM-D), Hamilton Rating Scale for Anxiety (HAM-A), UPDRS part 2 (UPDRS-II), and 39-item Parkinson’s Disease Questionnaire (PDQ-39) scores. Assessments were done at baseline (T0), 12 weeks (T1), 24 weeks (T2) and 36 weeks (T3). Results: Generalized estimating equation analyses revealed that PCG group had significantly better improvement in UPDRS-III score at T1, T2 and T3 (time-by-group interaction, T1: β, −0.92 [95% CI, −1.59 to −0.25; P = 0.01]; T2: β, −2.08 [95% CI, −2.90 to −1.27; P < 0.001]; T3: β, −4.54 [95% CI, −5.37 to −3.71; P < 0.001]). PCG group showed a greater decrease (rate of disease change) in the total UPDRS score between T0 and T2 (−2.23 [95% CI, −2.72 to −1.73; P < 0.001] points per week vs. −0.21 [95% CI, −0.80 to 0.39; P = 0.50] points per week in the placebo group, P < 0.001). Ameliorations of SCOPA-AUT, PDSS, HAM-D, HAM-A, UPDRS-II and PDQ-39 scores were also observed. Conclusion: PCG had a long-lasting and extensive symptomatic efficacy for both motor and non-motor symptoms of PD with good tolerance. Trial registration: Chinese Clinical Trial Register, ChiCTR-INR-17011949.